Augmented reality in tourism atractives: an analisys based on the Technology acceptance Model - Xavier, Isabelle da Fonsêca (2024)
Augmented Reality (AR), a technological tool that allows the insertion of virtual elements into the real world, can enhance the tourist experience by acting as a guide and secondary informative entertainment. Therefore, the present paper aims to analyze the perception of factors that influence the intention to use augmented reality in tourist attractions, based on the Technological Acceptance Model (TAM). The methodology used was descriptive-exploratory, with a quantitative approach, and the questionnaire was applied to 112 university students. For data analysis, the Structural Equation Modeling (SEM) technique was utilized through the SPSS v.23 software, AMOS package, to test the proposed model composed of five hypotheses. The results of the structural model indicate that the Intention to use Augmented Reality is directly influenced by Utility and Attitude, as well as pointing out the influence of Ease of Use in relation to Utility. It is concluded that the intention to use AR in a tourist attraction is greater when one considers its useful use and has a positive attitude towards it.